Family matters: A systematic review and meta-analysis on the efficacy of family-oriented interventions for children with acquired brain injuries. (February 2023) - Shen, Jiabin; Zhao, Siman; Horn, Timothy; Benkart, Rebekah; Busch, Tyler; Vrabec, Alison; Taylor, H. Gerry
Abstract: Introduction: Acquired brain injury (ABI) is a leading cause of disability among children. An increasing number of programs have emerged to involve family members as an integral component of post-ABI rehabilitation. This study aimed to conduct a systematic review and meta-analysis of such programs among children with ABI. Methods: Following PRISMA guidelines, search among six databases (PsycINFO, PsycARTICLES, Scopus, Web of Science, PubMed, Cochrane CENTRAL) was conducted, followed by abstract/full-text screening and data extraction. Hedge's g was computed for effect sizes. The risk of bias was assessed using Cochrane guidelines. Meta-regression analyses were conducted on six moderators. Results: A total of 32 studies (reported in 37 articles) were included in the qualitative analysis. Meta-analysis of 20 studies showed a positive small-to-medium effect of family-oriented interventions on child and parental outcomes but not on family functioning. Study design moderated the effect sizes of parent outcomes. Conclusions: This study synthesized the latest empirical evidence of family-oriented rehabilitation programs for pediatric ABI across interventional strategies, study designs, and outcomes. The findings suggested an overall beneficial impact of such programs on both the pediatric patients and their caregivers. Highlights: A systematic review on family-oriented pediatric ABI rehabilitation programs A positive small-to-medium effect was found on child and parental outcomes No significant effect was found on family functioning outcomes. Study design was found as a significant moderator of intervention effects